2020
DOI: 10.24840/2183-6493_006.001_0001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oat Hulls on Biodegradation of Biopolymer from Polylactic Acid

Abstract: The production of biopolymers has been shown to be one of the most viable alternatives for the reduction of the use of conventional plastics. The oat hulls are a by-product with great ability to be incorporated into the production of biopolymers since it is a lignocellulosic compound. The lignin present in its composition can improve the strength of the material, however, it can also hamper its degradation. The aim of this study was to evaluate the degradation levels of composites produced from starch and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The same happened with Silva et al. (2020) and Bilck et al. (2021) and this behavior may be due to incomplete gelatinization of the starch present in the films during processing, because the high concentration of starch in the blend.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The same happened with Silva et al. (2020) and Bilck et al. (2021) and this behavior may be due to incomplete gelatinization of the starch present in the films during processing, because the high concentration of starch in the blend.…”
Section: Resultssupporting
confidence: 75%
“…The formulations were chosen based on the studies of Silva et al. (2020) with minor modifications. Initially, glycerol (19%) was manually homogenized with PBAT (30%) and cassava starch (51%) (w/w/w).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation of the biodegradable materials (Table 1) was based on Silva et al (2020a) and used cassava starch (General Mills Brasil Alimentos Ltda, Paranavaí, Brazil), poly (lactic acid) (PLA) REVODE® 201-Zhejiang Hisun Biomaterials Co, China), micronized oat hulls (SL Alimentos-Mauá da Serra, Paraná, Brazil) (4.64 g 100 g -1 ash, 3.95 g 100 g -1 protein, 2.12 g 100 g -1 of lipid, 23.13 g 100 g -1 of cellulose, 26.25 g 100 g -1 of hemicellulose and 3.80 g 100 g -1 of lignin) and glycerol (Dinâmica Química Ltda, Brazil). The cassava starch and oat hulls were used because of their low cost compared with pure PLA, and the glycerol was used as a plasticizer (SILVA et al, 2020a). The starch, glycerol, PLA, and oat hull were mixed according to the proportions shown in Table 1 and extruded in a single-screw extruder (BGM,Brazil) to produce cylindrical strands.…”
Section: Methodsmentioning
confidence: 99%
“…According to the organic waste characterization (Table 2), it was not possible to meet the C/N ratio of 30:1, considered ideal to start the composting process (Kiehl, 1985), because this proportion was impracticable to assembly the reactors and to homogenize the wastes, it means that it would be necessary too much tree pruning. Other studies have also reported good performances in composting organic materials with C/N ratios below 19:1 (Sbizzaro et al, 2017;Silva et al, 2020a). Thus, other C/N ratios were tested, such as 19:1, 18.5:1, and 18:1 (Table 3).…”
Section: Methodsmentioning
confidence: 99%